Studi Komparatif Pelaksanaan Hukum Likuidasi Perseroan Terbatas oleh RUPS dalam Hukum Indonesia dan Malaysia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This study aims to compare the implementation of liquidation law for Limited Liability Companies (PT) by the General Meeting of Shareholders (GMS) in Indonesia and Malaysia. In Indonesia, the regulation is governed by Law Number 40 of 2007 in conjunction with Law Number 11 of 2020, while in Malaysia, it is governed under the Companies Act 2016. Although both legal systems share the fundamental principle of protecting creditors and shareholders, their approaches differ significantly. Indonesia’s civil law system emphasizes procedural formalism, while Malaysia’s common law system focuses more on solvency and active creditor involvement. This comparative study finds that Malaysia's practices offer greater administrative efficiency and accountability, which could serve as a model for corporate law reform in Indonesia. The findings aim to support the development of more adaptive, transparent regulations aligned with good corporate governance principles.